Comparison of seismic provisions of Andean countries - Mattos-Rodriguez, Adriana; Barraza, Stevens; Verbel Almario, Camilo (International Journal of Engineering and Technology, 2020)
This paper presents a seismic provisions comparison used in the countries of the Andean region. A brief summary of the Andean region seismicity, showing historical seismicity and the probability of earthquake occurrence in each Andean country and the overall zone is pre-sented; then a seismic provisions comparison is presented in tables taking into account the seismic hazard according to the peak ground acceleration, the site effects according to the soil classification and response spectra pseudo-acceleration. Finally, a static analysis of seismic force is carried out for each country in an intermediate-to-high seismic zone, the base design shear force is computed, and the results are compared.Â
Keywords: Seismic Provisions; Historical Seismicity; Shear Base Force; Andean Region; Building Code.